Microarray and genetic analysis reveals that csa‐miR159b plays a critical role in abscisic acid‐mediated heat tolerance in grafted cucumber plants. (13th June 2016) - Li, Hao; Wang, Yu; Wang, Ze; Guo, Xie; Wang, Feng; Xia, Xiao‐Jian; Zhou, Jie; Shi, Kai; Yu, Jing‐Quan; Zhou, Yan‐Hong
Abstract: Root‐shoot communication plays a vital role in plant growth, development and adaptation to environmental stimuli. Grafting‐induced stress tolerance is associated with the induction of plentiful stress‐related genes and proteins; the mechanism involved, however, remains obscure. Here, we show that the enhanced tolerance against heat stress in cucumber plants with luffa as rootstock was accompanied with an increased accumulation of abscisic acid (ABA), down‐regulation of a subset of microRNAs (miRNAs) but up‐regulation of their target genes and CsHSP70 accumulation in the shoots. Significantly, luffa rootstock and foliar application of ABA both down‐regulated csa‐miR159b and up‐regulated its target mRNAs CsGAMYB1 and CsMYB29 ‐like and CsHSP70 accumulation in cucumber, while ectopic expression of csa‐miR159b led to decreased heat tolerance, AtMYB33 transcript and AtHSP70 accumulation in Arabidopsis plants. Taken together, our results suggest that root‐originated signals such as ABA could alter miRNAs in the shoots, which have a major role in the post‐transcriptional regulation of the stress‐responsive genes.